Downregulation of DOCK1 sensitizes bladder cancer cells to cisplatin through preventing epithelial–mesenchymal transition - Chen D; Chen W; Jiang H; Yang H; Wang Y; Chen J (Dove Medical Press, 2016)
Da-jin Chen,1–3,* Wei Chen,4,* Hong Jiang,1–3 Hao Yang,1–3 Yu-cheng Wang,1–3 Jiang-hua Chen1–3 1Kidney Disease Center, The First Affiliated Hospital, Zhejiang University School of Medicine, 2Key Laboratory of Nephropathy, 3Kidney Disease Immunology Laboratory, The Third Grade Laboratory, State Administration of Traditional Chinese Medicine, 4Department of Hepatobiliary Surgery, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang Province, People’s Republic of China *These authors contributed equally to this work Abstract: During the past several decades, resistance to single or multiple anticancer agents has posed a great challenge in cancer therapy. Dedicator of cytokinesis 1 (DOCK1), the first identified member in DOCK family, plays diverse roles in cellular processes, including tumorigenesis. In this study, we explored the biological role of DOCK1 in the chemotherapeutic resistance in bladder cancer and its underlying mechanism. Our results showed that the bladder cancer cell lines UM-UC-3 and J82 with higher DOCK1 are more resistant to cisplatin, whereas B87 cells with the lowest expression of DOCK1 exhibited the highest sensitivity to cisplatin. Downregulation of DOCK1 with small interfering RNA (siRNA) increased the cisplatin sensitivity in bladder cancer cells. Moreover, treatment with cisplatin induced epithelial–mesenchymal transition (EMT), while transfection with Twist siRNA restored the chemosensitivity to cisplatin. In addition, we found that downregulation of DOCK1 reversed EMT program in bladder cancer cells. However, cotransfection with DOCK1 siRNA could not further enhance the cisplatin sensitivity and cellular phenotypic changes in tumor cells. Taken together, these results demonstrate that downregulation of DOCK1 could increase the chemosensitivity in bladder cancer cells via preventing cisplatin-induced EMT, suggesting that DOCK1 may serve as a potential therapeutic target in bladder cancer. Keywords: bladder cancer, epithelial–mesenchymal transition, drug resistance, DOCK1